Reform on The Marriage Age Limit by Jakarta Women's Health Organizations in Maqāṣid al-Syarī‘ah Perspective - Kamarusdiana, Kamarusdiana; Farohah, Naili (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2022)
This study aimed to determine the factors of child marriage and the age limit for marriage in the legislation and to analyze the arguments of Yayasan Kesehatan Perempuan in opposing and preventing child marriage cases through a judicial review of the Marriage Law at the Constitutional Court in terms of maqāṣid al-syarī‘ah. The research method used in this research is normative legal research, which aims to examine legal principles and written legal sources. The primary data source was obtained from the arguments of Women's Health organizations in the trial process at the Constitutional Court Number 30-74/PUU-XII/2014. Data which was analyzed in the study was collected through observation and interviews. The results of this study proved that the factors causing child marriage in Indonesia are mostly due to poverty, low level of education, conflict in the household, community traditions and religious understanding such as efforts to avoid adultery as well as unfavored environmental factors. Prevention of child marriage carried out by the Women's Health Foundation is in accordance with the objectives of maqāṣid al-syarī‘ah which include religious maintenance, offspring maintenance, soul maintenance, mind maintenance and property maintenance.